Conditional Control of Instrumental Avoidance by Context Following Extinction - Campese, Vincent D.; Brannigan, Lauren A.; LeDoux, Joseph E. (Frontiers in Behavioral Neuroscience, 2021)
Using rodents, three training arrangements (i.e., ABB vs ABA, AAA vs. AAB and ABB vs ABC) explored whether extinction influences the expression of avoidance in a manner controlled by context. Retention testing following extinction showed that more avoidance responding (i.e., renewal) was observed when extinguished cues were tested outside of the context where they had undergone extinction. In contrast, response rates were significantly lower when stimuli were tested within the context where extinction learning had occurred. These findings add to the emerging literature assessing the role of Pavlovian extinction processes in the development of instrumental avoidance responding by demonstrating conditional control over extinguished responding by context. This study was conducted using a within-subjects approach that minimized the potential for context-outcome associations to bias responding, and thus, reflects hierarchical control over behavior based on the specific associative status of each tested cue in each training context.